Can agricultural aspirations influence preferences for new technologies? Cropping systems and preferences for high-efficiency irrigation in Punjab, Pakistan - Bell, Andrew R.; Ward, Patrick S.; Ashfaq, Muhammad; Davies, Stephen (International Food Policy Research Institute, 2017)
In the face of increasing environmental stresses, there is a critical need to improve water-use efficiency in many arid and semiarid agroclimatic zones. Drip irrigation is a high-efficiency irrigation technology that can improve water-use efficiency in currently irrigated areas and transform areas that are not otherwise irrigable in practice. Although adoption of drip irrigation is growing rapidly in India, adoption is low in neighboring Pakistan. The authors of this paper undertook a discrete choice experiment framed around the hypothetical subsidized purchase of a drip irrigation system in four districts of Punjab, Pakistan. The nonrepresentative sample of adopters and nonadopters in the study districts identified a clear increase in the valuation of drip systems in the first several years following adoption. This finding suggests that farmers may be unaware of the opportunities for the use of drip irrigation on their farms or the benefits that may accrue from such use. In addition, farmers’ aspirations for cropping systems under drip were better predictors of the valuation of drip systems than were current cropping patterns, implying that a different agricultural landscape might reasonably emerge under improved adoption of drip. Aspirations differed across the different agroecological zones and water regimes captured by this study. Aspirations to substitute wheat crops for fruits and vegetables were associated with a higher appreciation of the subsidy level, whereas aspirations to expand wheat were associated with a higher appreciation of the area covered by the drip initiative; together, these findings imply a degree of control over the extent of wheat production in the landscape via careful design of the drip subsidy program. Although the penetration of drip irrigation is not yet sufficient to draw inferences from a representative sample, these results suggest a number of ways in which drip irrigation may transform Pakistan’s agricultural landscape